2022
DOI: 10.3389/fbioe.2022.1096054
|View full text |Cite
|
Sign up to set email alerts
|

Engineered cell culture microenvironments for mechanobiology studies of brain neural cells

Abstract: The biomechanical properties of the brain microenvironment, which is composed of different neural cell types, the extracellular matrix, and blood vessels, are critical for normal brain development and neural functioning. Stiffness, viscoelasticity and spatial organization of brain tissue modulate proliferation, migration, differentiation, and cell function. However, the mechanical aspects of the neural microenvironment are largely ignored in current cell culture systems. Considering the high promises of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 187 publications
0
4
0
Order By: Relevance
“…For conventional PDMS, Wang et al [31] reported YMs ranging from 570 kPa to 3.7 MPa. Furthermore, for applications in which the Young's modulus is important, such as cell microenvironments and deformable structures, it is essential to measure it in aqueous environments to unveil possible correlations (e.g., for studies about the relationship between a material's Young's modulus and cell differentiation [22,32,33]). The effect of swelling on the Young's modulus is indeed crucial for biological applications, as, in such circumstances, the IP-PDMS is in contact with liquids.…”
Section: Mechanical Characterisation Of Two-photon-polymerised Ip-pdm...mentioning
confidence: 99%
See 2 more Smart Citations
“…For conventional PDMS, Wang et al [31] reported YMs ranging from 570 kPa to 3.7 MPa. Furthermore, for applications in which the Young's modulus is important, such as cell microenvironments and deformable structures, it is essential to measure it in aqueous environments to unveil possible correlations (e.g., for studies about the relationship between a material's Young's modulus and cell differentiation [22,32,33]). The effect of swelling on the Young's modulus is indeed crucial for biological applications, as, in such circumstances, the IP-PDMS is in contact with liquids.…”
Section: Mechanical Characterisation Of Two-photon-polymerised Ip-pdm...mentioning
confidence: 99%
“…The ability to tune the Young's modulus, in this case, was limited to 2PP polymers featuring GPa Young's moduli, which have already been extensively used for cell mechanobiology [17][18][19] and in vitro disease modelling applications [20,21]. The main focus of the present work is, on the other hand, to focus on the tuneable mechanical properties and the achievable feature resolution of a soft (kPa-MPa YM) elastomeric material, IP-PDMS, which could find application in the context of neuronal engineered microenvironments [22] as the brain is one of the softest tissues in the body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of an appropriate microenvironment for the long-term in vitro culture of brain cells is still an unresolved question in neurobiology and tissue engineering [10,11]. It relates to the complexity of the extracellular composition in the brain tissue, different metabolic profiles and requirements in neuronal, glial, and endothelial cells, significant effects of developmental aspects, and the variability of current brain tissue in vitro models (isolated cells cultured in a 2D-or 3D-environment, brain-on-chip microfluidic models, organotypic slices, cerebral organoids, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…A 3D cell culture approach allows to recreate the specific environment that cells require in a controlled in vitro setting. [ 1,2 ] There are many additive manufacturing approaches to create polymeric or hydrogel “scaffolds”, which are structures that support cells in 3D. [ 3 ] Among these methods, two‐photon polymerization (2PP) is a technique widely used in the cell mechanobiology field [ 4,5 ] since it can manufacture structures in the submicrometric range.…”
Section: Introductionmentioning
confidence: 99%